Evaluation of Subcatchments in the Upper Damodar Valley for Undertaking Soil Conservation Measures on Priority Basis - Sen, P; Bhattacharya, P.B.; Mukherjee, R.K.; Roy, D.K. (Journal of Soil and Water Conservation, 2022)
The Upper Damodar Valley above the Panchet and Maithon dams of the D.V.C. extends over an area of about 7000 sq. miles, lying mostly in Bihar and partly in West Bengal and is comprised of cultivated upland, cultivable upland, waste land, denuded forest land, wooded forest land and gullied area lying both- inside and outside the foiests, each being under different conditions of erosion, besides large tracts of bunded paddy fields which are less susceptible to erosion. For initiating soil conservation measures in the Valley it is necessary to locate and specify the highly erodible areas and take up conservation measures in the most vulnerable spots at the first instance. Attempts to ascertain such areas were first made by Iyenger (1963) on the basis of slope and vegetation conditions and also by the Soil Conservation Department of D.V.C., on the basis of percentage of total erodible areas in each subcatchment. In the present paper an attempt has been made to evaluate the subcatchments on the basis of effective erosion conditions prevailing in each subcatchment at the end of the Third Five Year Plan period.